Notes on the taxonomy of mountain viscachas of the genus Lagidium Meyen 1833 (Rodentia: Chinchillidae) - Teta, Pablo; Lucero, Sergio O (THERYA, 2017)
Mountain viscachas of the genus Lagidium Meyen 1833 are medium-to-large hystricomorph rodents (1.5 -- 3 kg) that live in rocky outcrops from Ecuador to southern Argentina and Chile. Lagidium includes more than 20 nominal forms, most of them based on one or two individuals, which were first described during the 18th and 20th. Subsequent revisions reduced the number of species to three to four, depending upon the author. Within the genus, Lagidium viscacia (Molina, 1782) is the most widely distributed species, with populations apparently extended from western Bolivia to southern Argentina and Chile. We reviewed > 100 individuals of Lagidium, including skins and skulls, most of them collected in Argentina. We performed multivariate statistical analysis (i. e., principal component analysis [PCA], discriminant analysis [DA]) on a subset of 55 adult individuals grouped according to their geographical origin, using 16 skull and tooth measurements. In addition, we searched for differences in cranial anatomy across populations. PCA and DA indicate a moderate overlap between individuals from southern Argentina, on one hand, and northwestern Argentina, western Bolivia and northern Chile, on the other. The external coloration, although variable, showed a predominance of gray shades in southern Argentina and yellowish gray in northwestern Argentina. Specimens of southern Argentina were characterized by their bigger overall size, nasals expanded in its front half, and narrow dorsal root of the zygomatic process of the maxillary, while those of northwestern Argentina were smaller, with nasals lacking expansions and the dorsal root of the zygomatic process of the maxillary broad. Our study provides coincident results from quantitative and qualitative morphology that allow us to clearly differentiate southern Argentinean populations of Lagidium viscacia from those of northwestern Argentina and western Bolivia. The oldest available name for the populations from southern Argentina, sometimes referred as L. boxi, is moreni, a taxon with an unclear type locality. The status of the populations from northwestern Argentina and western Bolivia is relatively more complex, since at least eight nominal forms were described from this general area and because our sampling is far from being extensive. In addition, is also unclear if these populations correspond to one or more species, as well as their degree of differentiation from L. viscacia s. s. Without analyzing topotypes of all nominal forms and adequate samples across the entire distribution range, it is premature to put forward a formal taxonomic proposal; as such, at this moment we prefer to maintain those populations from northwestern Argentina, western Bolivia and central Chile under L. viscacia.